Neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio as risk factors for mortality in Peruvian adults with chronic kidney disease - Umeres-Francia, Gianfranco Eddú (2022)
Objective: To assess the association between the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) with all-cause mortality in Peruvian patients with chronic kidney disease (CKD) attending a tertiary hospital. Methods: We conducted a retrospective cohort study in adults with CKD in stages 1–5. The outcome variable was mortality and as variables of exposure to NLR and PLR. Both ratios were categorized as high with a cutoff point of 3.5 and 232.5, respectively. We carried out a Cox regression model and calculated crude and adjusted hazard ratios (HR) with their 95% confidence interval (95% CI). Results: We analyzed 343 participants with a mean age of 78.3 (± 11.9) years and 62.9% (n = 216) men. The median follow-up time was 2.45 years (2.08–3.08), and the frequency of deaths was 17.5% (n = 60). The mortality of patients with high NLR was 28% compared to 15.7% of the group with normal NLR, and the mortality was 35.7% in those with high PLR and 15.6% in those with normal PLR. In the crude analysis, the high NLR and PLR were significantly associated with all-cause mortality (HR = 2.01; 95% CI 1.11–3.66) and (HR = 2.58; 95% CI 1.31–5.20). In the multivariate model, after adjusting for age, sex, serum creatinine, albumin and hemoglobin, the high NLR and PLR remained as independent risk factors for all-cause mortality (aHR = 1.97; 95% CI 1.05–3.69) and (aHR = 2.62; 95% CI 1.25–5.51), respectively. Conclusion: Our study suggests the relationship between high NLR and PLR with all-cause mortality in patients with CKD.